Summation and product formulae on trigonometric functions - Wei, Chuanan; Gong, Dianxuan (Utilitas Mathematica, 2014)
By means of derivative operator, integral operator, binomial theorem and binomial inversions, several interesting summation and product formulae on trigonometric functions are studied.